Knowledge, attitudes, practices of occupational accident prevention and related factors among rice farmers in Northern Vietnam - My Ha Nguyen; Toan Van Ngo; Anh Quynh Tran; Linh Gia Vu; Nga Thu Phan; Son Truong Pham; Bach Xuan Pham; Tu Duc Pham; Hai Minh Vu (PLoS ONE, 2025)
Background This study aimed to assess rice farmers’ knowledge, attitudes, and practices (KAP) regarding the prevention of occupational accidents, along with identifying related factors. Methods An analytic cross-sectional study was conducted in six rural communes in Thai Binh province, targeting rice farmers aged 18 and older. A structured KAP questionnaire on occupational accident prevention was developed and pilot-tested with 168 participants. Knowledge scores ranged from 0–20 (1 point per correct answer), attitudes from 9–45 (5-point Likert scale), and practices from 17–85 (5-point frequency scale). Higher scores indicated better outcomes. Tobit regression was used to examine factors influencing KAP, accounting for the bounded nature of these scores. Results Among the 1,171 rice farmers surveyed, 17.5% had experienced an occupational accident in the six months prior to the study, most commonly involving cuts from sharp tools, falls during fieldwork, or injuries from handling machinery. The average knowledge score on accident prevention was 13.82 ± 4.58 points. The average attitude score regarding accident prevention was 34.47 ± 4.73 points, with the highest scores reflecting a strong emphasis on personal safety in rice farming. Conversely, the lowest scores were related to the perceived importance of seeking immediate medical aid after an accident. The average score for practices related to accident prevention was 63.63 ± 2.22 points. The study found that better KAPwere associated with a lower incidence of occupational accidents. Conclusion This study highlights the need for comprehensive health education programs to enhance rice farmers’ KAP in preventing occupational accidents, thereby reducing the risk and impact of such incidents in this population.